(untitled) (Bangladesh Heart Journal, 2020)
Background: Cardiovascular disease, and ischemic heart disease (IHD), is a major cause of morbidity and mortality in the very elderly patients (>80 years) worldwide. These patients represent a rapidly growing cohort presenting for percutaneous coronary intervention (PCI), now constituting more than one in five patients treated with PCI in real-world practice. Furthermore, they often have greater ischemic burden than their younger counterparts, suggesting that they have greater scope of benefit from coronary revascularization therapy. The elderly usually has higher prevalence of co morbidities and more often experience complications during and after revascularization procedures. Our aim was to evaluate clinical outcomes of PCI in patients older than 80 years, compared to their younger counterparts. Materials and methods: From July 2017 to July 2018 we included 212 patients with IHD purposively in Cardiology department of National Institute of Cardiovascular Diseases undergone PCI who were divided into 2 groups according to age: e” 80 years (n = 74) and < 80 years (n = 138). Baseline clinical characteristics, indications for coronary intervention, in hospital outcomes were obtained. Study endpoint were Renal impairment, MI, LVF, emergency revascularization and death. Results: Very elderly patients were more frequently male (86%) and nonsmoker at present (41% vs. 63%, p=0.003), had higher prevalence of hypertension (60% vs. 50%, p<0.13), and more often presented with NSTEMI (54% vs. 23%, p<0.001). Elderly group had higher incidence of TVD and LM disease (36% vs. 26% and 9.5% vs. 2.9%, p=0.07) and more incidence of ostial (16.2% vs.5.1%,p=0.007) and calcified lesions (31.1% vs. 14.5%, p=0.004). Procedural success (TIMI III) were high in both groups, but still lower in the elderly as compared to younger group (95% vs. 97%, p=0.65). Very elderly patients had higher incidence of post PCI bleeding, CIN, MI, LVF and death (9.5% vs.6.1%, 8.2% vs.3.7%, 6.8% vs.5.8%, 9.5% vs. 5.1% and 5.4%vs.3.6%,p=0.07), whereas emergency revascularization were higher in younger group (5.4% vs. 6.5%, p=0.07). Conclusion: Very elderly patients aged ≥80 years face more vascular site complications during PCI, usually have more LM and TVD with more ostial and calcified lesions in comparison with younger group. Though procedural success is similar with younger group, they face more post PCI CIN, LVF and MI. Repeat revascularization was higher in younger group. Bangladesh Heart Journal 2020; 35(1) : 61-65